TECHNOLOGY-INTEGRATION IN EFL CLASSROOM: Augmentation Language Learning Activities in Puentedura’s SAMR Framework - Isry Laila Syathroh (JOEL: Journal of Educational and Language Research, 2022)
Technology's rising prevalence seems to have an influence on many features of social life today. In terms of education, it brings potential opportunities for teachers to experiment with new means of providing lessons by integrating technology into their classrooms. The SAMR (substitution, augmentation, modification, and redefinition) model proposed by Puentedura (2006) was used to describe how technology was integrated into EFL learning activities. This research was conducted in one Indonesian vocational school with one EFL teacher and 36 students using a qualitative method. A two-block (14 meetings) of classroom participatory observation was conducted to address the research aim. It was discovered that approximately 84 percent (12 meetings) of technology integration activities were graded as augmentation level. It means that technology can be used to supplement conventional teaching resources while providing major benefits to students' experiences.